2012
DOI: 10.1111/j.1365-2648.2012.06029.x
|View full text |Cite
|
Sign up to set email alerts
|

A model for predicting acute and chronic fatigue in Chinese nurses

Abstract: Acute and chronic fatigue is affected by different factors and nurse managers should generate specific interventions to decrease them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
53
1
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(64 citation statements)
references
References 50 publications
9
53
1
1
Order By: Relevance
“…The levels of chronic fatigue, acute fatigue and inter‐shift recovery were examined in three studies (i.e. four articles) using the Occupational Fatigue Exhaustion Recovery scale (Barker & Nussbaum, ; Fang et al, ; Fang et al, ; Sagherian et al, ). One study measured the level of chronic fatigue using the Standard Shift Work Index (Ferri et al, ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The levels of chronic fatigue, acute fatigue and inter‐shift recovery were examined in three studies (i.e. four articles) using the Occupational Fatigue Exhaustion Recovery scale (Barker & Nussbaum, ; Fang et al, ; Fang et al, ; Sagherian et al, ). One study measured the level of chronic fatigue using the Standard Shift Work Index (Ferri et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…One article reported a significant relationship between the number of night and evening shifts and fatigue (Fang et al, ), with the number of night and evening shifts per month being positively associated with both acute and chronic fatigue, and negatively associated with inter‐shift recovery. However, four articles reported no significant relationship between the number of night shifts and fatigue (Eldevik et al, ; Fang et al, ; Flo et al, ; Jung & Lee, ). Fang et al () found that the number of night and evening shifts per month had only indirect effects on both acute and chronic fatigue as well as on inter‐shift recovery.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although long working hours are not related to CFS, it might lead to lack of sleep and induced short‐term memory or impairment of concentration. Sleep insufficiency could also trigger mental problems (Zhai, Zhang, & Zhang, ) and aggravate fatigue symptoms (Fang, Qiu, Xu, & You, ). Our results indicated that Chinese nurses suffered more serious mental symptoms than physical symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…The OFER scale has previously been used to measure self-reported levels of fatigue among RNs (Chen, Davis, Daraiseh, Pan, & Davis, 2014;Fang, Qui, Xu, & You, 2013;Geiger-Brown et al, 2012). This 15-item instrument is comprised of three subscales: chronic fatigue, acute fatigue, and intershift recovery.…”
Section: Occupational Fatigue Exhaustion Recovery (Ofer) Scalementioning
confidence: 99%